Taurine depletion during fetal and postnatal development blunts firing responses of neocortical layer II/III pyramidal neurons - Hosoi, Yasushi; Akita, Tenpei; Watanabe, Miho; Ito, Takashi; Miyajima, Hiroaki; Fukuda, Atsuo (Frontiers in Molecular Neuroscience, 2022)
Fetal and infant brains are rich in maternally derived taurine. We previously demonstrated that taurine action regulates the cation-chloride cotransporter activity and the differentiation and radial migration of pyramidal neuron progenitors in the developing neocortex of rodent fetuses. Here we examined the effects of fetal and infantile taurine depletion caused by knockout of the taurine transporter Slc6a6 on firing properties of layer II/III pyramidal neurons in the mouse somatosensory cortex at 3 weeks of postnatal age, using the whole-cell patch-clamp technique. The membrane excitability under resting conditions was similar between the neurons in knockout mice and those in wildtype littermates. However, the frequency of repetitive spike firing during moderate current injection was significantly lower, along with lower membrane voltage levels during interspike intervals in knockout neurons. When strong currents were injected, by which repetitive firing was rapidly abolished due to inactivation of voltage-gated Na+ channels in wildtype neurons, the firing in knockout neurons lasted for a much longer period than in wildtype neurons. This was due to much lower membrane voltage levels during interspike intervals in knockout neurons, promoting greater recovery of voltage-gated Na+ channels from inactivation. Thus, taurine depletion in pyramidal neurons blunted neuronal responses to external stimuli through increasing the stability of repetitive firing, presumably mediated by larger increases in membrane K+ conductance during interspike intervals.